A Comparative Study on the Techniques, Tools and Materials for Indigenous Weaving in Ghana. (2nd January 2023) - Afriyie, Alex Osei; Frimpong, Charles; Asinyo, Benjamin Kwablah; Seidu, Raphael Kanyire
Abstract: Strip woven fabrics such as kente, kete and smock have continued to be precious cloths that promote the cultural heritage of the people in Ghana. These fabrics were originally woven for the royals, chiefs and special individuals in the society for specific events, but are currently being used by people from all walks of life for different purposes. Recent studies majored their investigation on the history and symbolism of indigenous fabrics, with little or no information on the distinguishing elements in the materials, tools, equipment and techniques employed across the communities engaged in the craft. This study seeks to unearth these differences and the similarities, all in a bid to deepen appreciation of the cultural value of these cloths. A descriptive multiple case study was conducted in Agotime-Kpetoe, Agbozume, Daboya and Bonwire which aided in gathering and analyzing field data. Field reports revealed that synthetic yarns are commonly used by Asante and Ewe weavers to produce the traditional cloth while weavers in Daboya use both synthetic yarns and indigo-dyed cotton yarns. The type of loom and the number of heald shafts determine the simplicity or complexity of weaves produced in Agotime-Kpetoe, Agbozume and Bonwire. There is no doubt that weaving activity and the resultant fabric continue to not only serve as a major source of income and employment for many but significantly maintain their unique relevance for many weavers and patrons. It is therefore worthy of whatever support and promotion it can enjoy from stakeholders. Further research studies and organized festivals are encouraged to document and exhibit the traditional cloth, materials and processes, a situation that is significant in preserving the philosophy and culture of the people.